The impact of product reviews and price on purchase intention for Skintific skincare products: Trust as a mediating variable - Rony Ariesta, Ghiva; Septrizola, Whyosi (Marketing Management Studies, 2025)
This research aims to determine the influence of product reviews, price, which is mediated by trust on buying interest at the State University in Padang City. The population is Padang State University (UNP), Andalas University (UNAND), and Imam Bonjol State Islamic University (UIN IB) with a sample size of 290 respondents. Data was collected using a questionnaire and data was processed using SmartPLS 4. The results are (1) Product reviews have a positive and significant influence on purchasing interest. (2) Price has a positive and significant influence on buying interest. (3) Product reviews have a positive and significant influence on trust. (4) Price has a positive and significant influence on trust. (5) Trust does not have a positive and significant influence on buying interest. (6) Product reviews do not have a positive and significant influence on purchasing interest through trust. (7) Price does not have a positive and significant influence on buying interest through trust.